Fishing Tourism can Support Fisher’s Livelihood and Fish Conservation in Nepal: A Value Chain Analysis - Gurung, Tek Bahadur; Thing, Amar (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Fishing tourism of recreational fisheries is a multibillion dollar outdoor activity. The fishing tourism in Nepal is yet to be systematized. Focusing on this need, the present paper attempts to pioneer how recreational fisheries in Nepal could be useful having commendable world renounced fish resources, luring pristine and suitable scenic landscapes for promoting fishing tourism. It is argued that fishing tourism should be systematically regularized and practiced in close collaboration with traditional ethnic fisher communities. Considering the potentiality, we elucidate the result of value chain analysis, arguing that promotion and streamlining of fishing tourism along with the traditional fishers could generate immense livelihood opportunities for resilience along with fish conservation. The value chain analysis showed that livelihood of fishers communities are likely to be enhanced by involving in fishing based tourism support services with fewer fishing activities, which in turn could be supportive to fish conservation. The present modality of promoting and systematizing fishing tourism might have implication to address the issues of poverty alleviation and resilience to fish conservation in many developing countries having similar socio-economic and agro ecological setups in Nepal. HYDRO Nepal Journal of Water Energy and Environment Volume- 18, 2016, January Page -55 to 60